Dative epitaxy of commensurate monocrystalline covalent van der Waals Moiré supercrystal - Bian, Mengying (2022)
Realizing van der Waals (vdW) epitaxy in the 1980s represents a breakthrough that circumvents the stringent lattice matching and processing compatibility requirements in conventional covalent heteroepitaxy. However, due to the weak vdW interactions, there is little control over film qualities by the substrate. Typically, discrete domains with a spread of misorientation angles are formed, limiting the applicability of vdW epitaxy. Here, the epitaxial growth of monocrystalline, covalent Cr5 Te8 2D crystals on monolayer vdW WSe2 by chemical vapor deposition is reported, driven by interfacial dative bond formation. The lattice of Cr5 Te8 , with a lateral dimension of a few tens of micrometers, is fully commensurate with that of WSe2 via 3 × 3 (Cr5 Te8 )/7 × 7 (WSe2 ) supercell matching, forming a single-crystalline moiré superlattice. This work establishes a conceptually distinct paradigm of thin-film epitaxy, termed "dative epitaxy", which takes full advantage of covalent epitaxy with chemical bonding for fixing the atomic registry and crystal orientation, while circumventing its stringent lattice matching and processing compatibility requirements; conversely, it ensures the full flexibility of vdW epitaxy, while avoiding its poor orientation control. Cr5 Te8 2D crystals grown by dative epitaxy exhibit square magnetic hysteresis, suggesting minimized interfacial defects that can serve as pinning sites.